Normal growth and development in a child with Baller-Gerold syndrome (craniosynostosis and radial aplasia). Issue 12 (December 1990) - Galea, P; Tolmie, J L
Abstract : The cardinal features of the Baller-Gerold syndrome (MIM *21860) are craniosynostosis and radial aplasia. Only 12 cases have been published and these are roughly divisible into two groups: cases without any additional abnormalities and cases with a broad range of additional features. We describe a boy with craniosynostosis and radial aplasia alone and highlight genetic counselling difficulties presented by a sporadic case of this rare syndrome.